Polynitrogen Bicyclic and Tricyclic Compounds as PDE4 Inhibitors - Claudia Vergelli; Agostino Cilibrizzi; Gabriella Guerrini; Fabrizio Melani; Marta Menicatti; Gianluca Bartolucci; Maria Paola Giovannoni; Letizia Crocetti (Applied Sciences)
We report here two new series of designed PDE4 inhibitors, the first one showing the quinoline scaffold recently investigated by us through a fragment-based drug design strategy, and the second consisting of pyrazolo [1′,5′:1,6]pyrimido[4,5-d]pyridazine derivatives. Both the new series were subjected to biological studies to assess their inhibitory effect on PDE4 enzymes, supported by molecular modelling experiments, to rationalize the different activities recorded in the in vitro tests. Interesting results were achieved for two compounds belonging to the tricyclic series, namely 10a and 10e, exhibiting IC50 = 62 and 175.5 nM, respectively. These results could represent the starting point for further studies with the aim of developing new and effective PDE4 inhibitors for biomedical investigations.